GE_GERICHTE P/8079/2016 vom 5. Oktober 2018 - GE Cour de justice (2018)
RAISON DE COMMERCE ; EXPLOITANT ; CONCURRENCE DÉLOYALE ; INDEMNITÉ(EN GÉNÉRAL) | LCD.4a.al1.leta; LCD.23.al1; LCD.2; CP.2; RTFMP.14.al1.lete; CPP.429.al1